Issues of countering nuclear terrorism and limiting human rights while repelling threats in the airspace - A.N. Metel’kov (Penza State University Publishing House, 2021)
Background. Anti-terrorist legislation in a crisis situation allows the Armed Forces, under certain conditions, to destroy aircraft hijacked by terrorists. The mechanism of legal regulation of such suppression is theoretically insufficiently developed and balances on the sharp line between constitutionality and ensuring the security of society and the state. The law does not take into account possible differences in the legal personality of passengers. The purpose of the research is to attempt to investigate the complex legal issues of suppressing terrorist attacks in the air against radiation hazardous objects using hijacked aircraft. Materials and methods. The article analyzes the norms of the basic Federal law “On Countering Terrorism” in terms of implementing the constitutional provisions on human rights and ensuring public safety when using weapons to eliminate the threat of a terrorist attack in the air and its suppression in relation to radiation-hazardous objects. The specific sociological and comparative legal methods used by the author allow us to compare certain elements of the legal subsystem of countering terrorism with constitutional and international legal provisions and approaches. Results. The analysis of the subjects’ powers of countering acts of nuclear terrorism indicates the need to improve the legal framework to provide a clearer and clearer legal basis for suppressing terrorist attacks using aircraft seized by terrorists. Conclusions. The prevention of acts of nuclear terrorism involving the use of aircraft seized by terrorists as an instrument of crime by destroying them requires the improvement of anti-terrorist legislation aimed at ensuring the suppression and minimization of possible negative consequences.